Study of leptospirosia in animal and livestock - N, Enkhtsetseg; B, Altankhuu; B, Narangerel (Mongolian Journal of Agricultural Sciences, 2019)
Leptospirosis is a zoonotic bacterial disease that affects vulnerable populations such as rural subsistence farmers and urban slum dwellers. Leptospirosis is an infectious disease caused by pathogenic organisms belonging to the genus leptospira, that are transmitted directly or indirectly from animals to humans. In Mongolian human cases of leptospirosis has not been reported yet and this zoonotic disease not well study. We had use the kit in order to detect Pomona, Tarassovi, Hebdomadis, Icterohaemorrhagiae, Grippotyphosa, Sejroe and Canicola serotype by Enzyme-linked immunosorbent assay (ELISA) test. We analyzed 397 samples of bovine serum by indirect ELISA. The bovine serum samples were collected from Selenge province, and out of 101 samples 2 were positive. And, out of 171 bovine 1 serum was positive in Tov province. In contrast, no positive samples detected in 137 swine serum. Linnodee leptospira /ireland/- ELISA kit can detect a swine Bratislava serotype and cattle Hardjo serotype. To detect Hardjo serotype, 397 samples of cattle serum and 137 samples of swine serum were investigated. The 29 serum of cattle were positive, which has 7.3% infection rate, and, only one swine sera was positive out of 137, that has 0.73% infection rate. The 137 swine serum were tested by ELISA, which can detect Leptospira Bratislava serotype; and 12 out of that were positive. This indicates 8.7% of all sample are positive. Total of 397 bovine sera were examined by ELISA and specific antibody against Pomona, Tarassovi, Hebdomadis, Icterohaemorrhagiae, Grippotyphosa, Sejroe and Canicola serotype detected in 0,75 % (3 sera samples). Hardjo serotype detected in 7.3 % (29 sera) of bovine samples and 7.6 % (1 serum) of 13 swine sera samples and furthermore, bratislava serotype antibody detected in 8.7% (12 sera) of the pigs included in our study. Our study indicates that risk of human leptospirosis infection through animal derived food consumption, soil and water contamination is present due to prevalence of hardjo and bratislava serotype in cattle and pig farms. These results correlates with study conducted by Odontsetseg N. PhD in 2005 which stated that Hardjo serotype of Leptospira interrogans was detected in cattle herd in our country and these suggest that leptospirosis is prevalent in certain regions of our country. Мал амьтны лептоспирозийн тандан судалгааны дүн Хураангуй: Мал амьтны гаралтай хүнсний бүтээгдэхүүн ус, хөрсөөр дамжин хүнд халдварладаг зооноз өвчин болох Лептоспирозийн танадан судалгааг Булган, Орхон, Сэлэнгэ, Төв аймгууд болон Улаанбаатар хот орчмоос цуглуулсан үхрийн 721, гахайн 169, зарим мэрэгч амьтдын 108, усны 22 нийт 1020 сорьцыг ийлдэс судлал болон молекул биологи, нян судлалын аргаар шинжлэв. Судалгааны дүнд шинжилгээнд хамрагдсан нийт 397 үхрийн сорьцны 32 буюу 8.06%, 137 гахайн сорьцны 13 буюу 9.4%-д нь L. pomona, L. tarassovi, L. hebdomadis, L. icterohaemorrhagiae, L. grippotyphosa, L. sejroe, L. canicola, L. hardjo, L. bratislava хэвшлүүдийн эсрэг үүссэн өвөрмөц эсрэгбием тус тус илрэв. Лептоспирозийн байгалийн дамжуулагч болох мэрэгчийн 108-н сорьцонд Полимериазан Гинжин Урвал (ПГУ) тавихад 8 сорьц буюу 7.4%-д нь лептоспирозийн G1, G2 генийн өвөрмөц бүтээгдэхүүн илэрсэн болно. Ийлдэс судлал, ПГУ- аар эерэг гарсан сорьцуудад үүсгэгч илрүүлэх нян судлалын шинжилгээ хийсэн боловч үүсгэгч өсгөвөрлөгдсөнгүй. Манай орны Орхон, Сэлэнгийн сав газар, Архангай, Төв аймаг, Улаанбаатар хот орчмын үхэр, гахай, мэрэгчидийн сорьц лептоспирозоор эерэг дүн үзүүлсэн нь манай орны мал амьтан, мэрэгчидэд өвчний халдварлалт байгааг харуулж байна. Түлхүүр үг: Leptospira, үүсгэгч, өвөрмөц эсрэгбием, ийлдсийн хэвшил, ген